Comparison of vocal load parameters by dosimetry in female teachers - Orellana Marambio, Patricio Alonso; Núñez Zamora, Alicia; Marín Garrido, Fabiola (Revista de Investigación en Logopedia, 2022)
Vocal load is defined as the amount of work done by the laryngeal mechanism over time. No studies of its differentiated assessment were found in the classroom and in the clinical simulation space. It is necessary to differentiate the results of the parameters: fundamental frequency, vocal intensity, and environmental noise in both contexts to promote an ecological perspective of the vocal health of teachers. The objective of this research is to determine the differences in the vocal load of a group of teachers from three educational establishments in the Metropolitan Region of Chile, in clinical and work simulation spaces. Cross-sectional comparative study of 26 preschool and basic education teachers without a history of vocal pathologies. The evaluation of the vocal parameters was carried out through a dosimeter. The ambient noise was evaluated by means of a sound level meter. The results showed significant differences of the three variables between the classroom and the simulated clinical space. There were also significant differences in intensity and ambient noise between teaching levels and number of students per room, with the intensity and noise being higher in the basic level rooms, compared to the preschool level. In conclusion, there is a higher vocal load in the classroom, defined by an increase in the fundamental frequency and intensity, compared to the simulated clinical space. This could be determined by ambient noise. It is suggested to carry out speech therapy intervention in the work context.